The Strong Fuzzy Henstock Integrals and Discontinuous Fuzzy Differential Equations - Yabin Shao; Huanhuan Zhang (Journal of Applied Mathematics)
We generalized the existence theorems and the continuous dependence of a solution on parameters for initial problems of fuzzy discontinuous differential equation by the strong fuzzy Henstock integral and its controlled convergence theorem.